Evaluasi Program Penanggulangan Stunting Pada Balita - Dewi Agustina; Suci Maghfirah; Rosida Sapriani Harahap; Nadia Amanda Azwa; Assyifa Deswita Mrp; Dwi Fanny Amanda; Faiqah Adnin Purba; Fadhlan Al Hafiz Mrp; Muhammad Raihan Pratama; Lilis Karlina Boangmanalu; Dinda Agus Tantri; Hairum Nafsiah Purba (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The problem of stunting among toddlers in Indonesia is still the focus of the public health agenda. Evaluation of stunting prevention programs is needed to identify program barriers and ensure their effectiveness in overcoming the problem of stunting in toddlers. To evaluate stunting prevention programs for toddlers in Indonesia and to provide recommendations and solutions in overcoming the problem of stunting in toddlers through a comprehensive approach involving various aspects of health and nutrition. The research method is a Systematic Literature Review, with data sources received from journals and research results published on Google Scholar, with journal criteria that match the research topic, using Indonesian and English, published in the last 5 years (2019-2023). The stunting prevention program for toddlers in Indonesia has been carried out with various activities such as monitoring toddlers, providing PMT, health education, nutritional counseling, and providing vitamins and minerals. Even though the program has been implemented, there are still obstacles such as delays in disbursement of BOK funds and lack of program effectiveness. Evaluation of this program is important to ensure the effectiveness and sustainability of the program in dealing with stunting in toddlers. It is important to carry out stunting prevention programs for toddlers in Indonesia to ensure the effectiveness and sustainability of the program in dealing with stunting problems. Solutions to overcome stunting require a comprehensive approach that includes access to nutritious food, nutrition education, access to health services, and improved sanitation.